Implementasi Surat Edaran Kemendikbud. No. 20 tahun 2020 Tentang Kebijakan Work from Home (WFH) - Pujiantoro Pujiantoro; Suwarno Suwarno; Teguh Pramono (Jurnal Indonesia Sosial Sains, 2022)
The unresolved COVID-19 pandemic has an impact on society. As a result, the government has announced various policies, one of which is the policy of limiting social activities. This research, describes, analyzes “SE Implementation. Ministry of Education and Culture. No. 20 of 2020 Regarding the Work from Home (WFH) Policy at PSDKU Malang State Polytechnic in Kediri City. This study uses a qualitative descriptive research method. The informants of this research were staff and lecturers, the research focused on Gorge Edward III theory, data collection techniques by interview, documentation and observation, matrix model research instruments, data analysis techniques with interactive model analysis, including: data collection, data condensation, data presentation, and conclusion. The results of the research show that the implementation went well. The constraining factor is an unstable internet network during online lectures. The supporting factors for its implementation are supporting human resources and health protocol supporting facilities.